Magnetic nanocatalysts: Synthesis and application in multicomponent reactions - Chen, Meng-Nan; Mo, Li-Ping; Cui, Zhen-Shui; Zhang, Zhan-Hui (Current opinion in green and sustainable chemistry, 2019)
The application of the magnetic nanocatalysts is a rapidly growing field for the development of sustainable and green processes. Magnetic separation not only avoids the need for catalyst filtration or centrifugation after completion of the reaction, but also provides practical techniques for recovering these catalysts. Multicomponent reactions are recognized as very powerful tools in synthetic organic and medicinal chemistry for the synthesis of the complex products in a single step from simple starting materials. The combination of magnetic nanocatalysts and multicomponent reactions will become an emerging strategic research area and is an ideal blend for the development of sustainable methods in green synthetic chemistry. This review focuses on the synthesis and application of magnetic nanocatalysts as novel task-specific catalysts for multicomponent reactions in recent years.